Modelling inflows in Ilarion reservoir, Greece, using HEC-HMS - Tică Eliza-Isabela; Popa Florica; Neagoe Angela; Popa Bogdan; Zorbas Miltiadis (E3S Web of Conferences)
This study investigates the application of the Hydrologic Modeling System (HEC-HMS) for simulating inflows to the Ilarion Reservoir, the first reservoir in the cascade of five along the Aliakmon River in northern Greece. The model is calibrated using observed meteorological and hydrological data to assess its performance and reliability in reproducing observed flows. Model accuracy is evaluated through statistical indicators such as the Nash-Sutcliffe Efficiency (NSE) and Percent Bias (PBIAS). The results demonstrate a satisfactory agreement between simulated and observed discharge, highlighting the model’s potential as a reliable tool for hydrological forecasting and water resource management in the region.